Pengaruh Kualitas Pelayanan dan Harga Terhadap Kepuasan Pelanggan pada Bengkel Online Supercar.Id Kota Tangerang Selatan - Ari Prayudi (Syntax Idea)
This study aims to determine how the influence of quality services and prices on customer satisfaction in online workshops supercar.id south tangerang. The research method used in the research This is a quantitative method with an associative approach, collection method the data used is a questionnaire questionnaire, with sampling using the solvency method. The analytical method used in this study are validity test, reliability test, normalitytest, multicollinearity test,test heteroscedasticity, autocorrelation test, simple linear regression test, linear regression test multiple, correlation coefficient test, coefficient determination test, T test, and F test. Results research hypothesis testing partially variable service quality (X1) t value obtained > t table (17,383 > 0.2072) this is also strengthened with a significance value of 0.001 <0.005. This means that the quality of service has an effect positive on customer satisfaction. Price variable statistical test (X2) is obtained t count > t table (20.035 > 0.2072) this is also reinforced by the value significance 0.001 <0.05. This means that the price has a significant effect on customer satisfaction. Simultaneous hypothesis testing obtained the calculated f value > f table or (372,688 > 3.10) this is also strengthened by a significance value 0.001 <0.05. So it can be said that the quality of service and price significant effect simultaneously on customer satisfaction. Coefficient determination obtained R square value of 0.895, meaning the quality of service and prices together have a contribution of 89.5% influence on customer satisfaction. While the remaining 10.5% is influenced by factors others that were not examined in this study.